Macroeconomic variables affecting housing prices in Malaysia / Nor Farhana Suid and Nur Jafina Nabila Jaafar - Suid, Nor Farhana; Jaafar, Nur Jafina Nabila (Faculty of Business and Management, 2016)
In these recent years, Malaysia has experienced significant housing price appreciation and it caused a distress among citizens especially young generation as the prices of residential property nowadays are beyond the ability to acquire. This study intends to examine the macroeconomic variables would affect the housing prices in Malaysia. There are four macroeconomic variables which are Consumer Price Index (CPI), Gross Domestic Product (GDP), Interest Rate (IR) and Population (P) was taken into study, together with Malaysia Housing Price Index (MHPI). The data ranges from 1983 to 2015 on a yearly basis which comprises of 32 observations. In this study, EViews9 statistical tool is used in findings and data analysis process. The result shows that only Interest Rate has statistical significant relationship with Malaysia Housing Price Index (MHPI). This study aims to contribute and enhance the execution on scenario planning that related to unpredictable rise of house price in Malaysia as well as assist government and relevant parties in their decision-making process in conjunction of the continuous increasing of housing price is now a major concern.